Hydraulic Fracturing: A Critical Physical Geography Review. Issue 10 (October 2014) - Lave, Rebecca; Lutz, Brian
Abstract Taking a critical physical geography approach, this article provides the first side‐by‐side review of the physical and social literature on hydraulic fracturing or "fracking" as it is frequently referred to. We note the striking disparities between the physical science literature's description of the relatively manageable impacts of fracking and the almost apocalyptic tone taken in some popular press and critical social science literature. We argue that these disparities may be a result of the dramatic shift in the geography of energy production in the US. The rise of fracking has redistributed environmental injustices beyond traditional national sacrifice zones, such as Appalachia, and towards regions that in many cases are wealthier than Appalachia and have not recently borne the brunt of energy production, causing profound social, cultural, and economic shocks. Reviewing the physical and social science literature together suggests that we reconsider the fracking research agenda. Studies of the physical impacts of hydraulic fracturing should be expanded to address communities' concerns about habitat fragmentation and the impacts of the myriad truck trips required to service fracking wells, neither of which currently are given much attention. Social science research on fracking could benefit from an increase in comparative work, assessing the relative economic and social impacts in regions where energy production is ramping up in relation to regions where it is declining.